Penerapan Metode Ceramah Untuk Meningkatkan Hasil Belajar PAI Siswa di SMK Negeri 8 Padang - Afrian Deni (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to determine whether the application of the lecture method can improve the learning outcomes of grade X students of Islamic Religious Education subjects on the aspect of Achieving Success Through Competing in Goodness and Work Ethic. The subjects in this study were grade XI students at SMK Negeri 8 Padang. This research is a Classroom Action Research (PTK) which consists of 2 cycles, namely cycle I, cycle II. Each cycle is a series of activities, each of which consists of 4 stages of planning, implementation, observation / observation and reflection. This Classroom Action Research uses data collection methods, namely oral tests, observation sheets and documentation. The data analysis used by comparing the achievement of learning outcomes for each cycle with a marked increase in the minimum completeness criteria (KKM) or using descriptive-qualitative. The results obtained from this study are an increase in the learning outcomes of class XI students of Islamic Religious Education subjects on aspects of the Qur'an Strengthening Harmony through Tolerance. The class average at the pre-cycle stage was 6.78, in cycle I it rose to 75.89, in cycle II it increased again to 83.75. And classical completeness at the pre-cycle stage was 22.2%, in cycle I it became 75.4%, in cycle II it increased again to 83.75%. Based on these learning outcomes, it can be concluded that through the lecture method can improve the learning outcomes of class XI students of Islamic Religious Education subjects in the aspect of Al-Qur'an Material Strengthening Harmony through Tolerance in the 2024-2025 academic year. Keywords: , , Islamic Education Material.